Assessment of Knowledge and Attitude of Women towards Hormonal Replacement Therapy during the Menopause - مصطفى, نسرين (Latakia University Journal -Medical Sciences Series, 2020)
Women menopause suffer from symptoms ranging from mild to severe, and Hormonal Replacement Therapy HRT is one of the important treatment options for these symptoms, which contributes to improving their quality of life, but their Knowledge and attitudes toward this type of treatment are a key factor in accepting and using it, Therefore, the current descriptive study was conducted to identify the Knowledge and attitude of 200 menopause women about HRT in the women's clinic at Tishreen University Hospital. They were chosen in an appropriate random sampling method, and data was collected using a questionnaire developed by the researcher. The results showed that the majority of women in the sample had a poor level of Knowledge about HRT. They do not know the concept of HRT, its benefits, side effects and contraindications, and that 77.5% of them have a neutral attitude towards HRT and 22% of them have a positive attitude towards it. The study recommended conducting educational courses for women in health centers about menopause and HRT in all its aspects, the need for specialized centers that provide care and advice for women of menopause, and conducting a broader and more comprehensive study at the country level to assess the information and trends of Syrian women about HRT.